A novel quorum sensing regulator LuxT contributes to the virulence of Vibrio cholerae - Yuehua Li; Junxiang Yan; Jinghao Li; Xinke Xue; Ying Wang; Boyang Cao (Virulence, 2023)
Vibrio cholerae is a waterborne bacterium that primarily infects the human intestine and causes cholera fatality. Quorum sensing (QS) negatively regulates the expression of V. cholerae virulence gene. However, the primary associated mechanisms remain undetermined. This investigation identified a new QS regulator from the TetR family, LuxT, which increases V. cholerae virulence by directly inhibiting hapR expression. HapR is a master QS regulator that suppresses virulence cascade expression. The expression of luxT increased 4.8-fold in the small intestine of infant mice than in Luria-Bertani broth. ΔluxT mutant strain revealed a substantial defect in the colonizing ability of the small intestines. At low cell densities, the expression level of hapR was upregulated by luxT deletion, suggesting that LuxT can suppress hapR transcription. The electrophoretic mobility shift analysis revealed that LuxT directly binds to the hapR promoter region. Furthermore, luxT expression was upregulated by the two-component system ArcB/ArcA, which responses to changes in oxygen levels in response to the host’s small intestine’s anaerobic signals. In conclusion, this research reveals a novel cell density-mediated virulence regulation pathway and contributes to understanding the complex association between V. cholerae virulence and QS signals. This evidence furnishes new insights for future studies on cholerae’s pathogenic mechanisms.